Awil xojaliǵi tálim baǵdari studentlerine inglis tilin clil texnologiyasi tiykarinda úyretiw (ILIM hám JÁMIYET, 2023)
This article discusses the benefits of using CLIL technology in developing the communication skills of young agricultural education students in presents classrooms.